Statistical Mechanics of Nonequilbrium Liquids - J. Evans, Denis (ANU Press, 2007)
During the 1980's there were many developments regarding the nonequilibrium statistical mechanics of dense classical atomic fluids. These developments have had a major impact on the computer simulation methods used to model nonequilibrium fluids. The present volume is, in part, an attempt to provide a pedagogical discussion of the statistical mechanical justification of these algorithms. There is a symbiotic relationship between theoretical nonequilibrium statistical mechanics on the one hand and the theory and practice of computer simulation on the other. Sometimes, the initiative for progress has been with the pragmatic requirements of computer simulation and at other times, the initiative has been with the fundamental theory of nonequilibrium processes. This book summarises progress in this field up to 1990.